H3K4me3 mediates the NF-κB p50 homodimer binding to the pdcd1 promoter to activate PD-1 transcription in T cells. (2nd September 2018) - Redd, Priscilla S.; Lu, Chunwan; Klement, John D.; Ibrahim, Mohammed L.; Zhou, Gang; Kumai, Takumi; Celis, Esteban; Liu, Kebin
ABSTRACT: PD-1 is a co-repressive receptor that curbs T cell activation and thereby serves as a protection mechanism against autoimmunity under physiological conditions. Under pathological conditions, tumor cells express PD-L1 as an adaptive resistant mechanism to suppress PD-1 + T cells to evade host immunosurveillance. PD-1 therefore is a key target in cancer immunotherapy. Despite the extensive studies of PD-1 expression regulation, the pdcd1 transcription machinery and regulatory mechanisms are still not fully understood. We report here that the NF-κB p50 homodimer is a transcription regulator of PD-1 in activated T cells. A putative κB sequence exists at the pdcd1 promoter. All five NF-κB Rel subunits are activated in activated T cells. However, only the p50 homodimer directly binds to the κB sequence at the pccd1 promoter in CD4 + and CD8 + T cells. Deficiency in p50 results in reduced PD-1 expression in both CD4 + and CD8 + T cells in vitro . Using an in vivo mixed bone marrow chimera mouse model, we show that p50 regulates PD-1 expression in a cell-intrinsic way and p50 deficiency leads to decreased PD-1 expression in both antigen-specific CD4 + and CD8 + T cells in vivo . The expression levels of H3K4me3-specific histone methyltransferase increased significantly, resulting in a significant increase in H3K4me3 deposition at the pdcd1 promoter in activated CD4 + and CD8 + T cells. Inhibition of H3K4me3 significantly decreased p50 binding to the pdcd1 promoter and PD-1 expression in a T cell line. Our findings determine that the p50-H3K4me3 axis regulates pdcd1 transcription activation in activated T cells.